VCSEL quick fabrication of 894.6 nm wavelength epi‐material for miniature atomic clock applications. Issue 1 (11th November 2022) - Baker, Jack; Allford, Craig. P.; Gillgrass, Sara.; Peach, Tomas.; Meiklejohn, James; Hentschel, Curtis; Meredith, Wyn; Powell, Denise; Sweet, Tracy; Haji, Mohsin; Davies, J. Iwan; Shutts, Samuel; et al.
Abstract: A vertical cavity surface emitting laser (VCSEL) quick fabrication (VQF) process is applied to epitaxial materials designed for miniature atomic clock applications (MACs). The process is used to assess material quality and uniformity of a full 100 mm (4‐inch) wafer against the stringent target specification of VCSELs for MACs. Target specifications in optical power (>0.6 mW) and differential efficiencies (<0.5 W/A) are achieved over large portions of a wafer; however, the variation in the oxide aperture diameter is shown to limit the yield. The emission of the fundamental mode at 894.6 nm at 70 ℃ $^{°}C$ is met over a significant area of the wafer for ∼4 μ $μ $ m aperture multi‐mode devices. The consideration of the on‐wafer variation reveals that further optimisation is required to increase the device yield to levels required for volume manufacture. Abstract : A VCSEL quick fabrication (VQF) process is applied to the epitaxial material designed for miniature atomic clock applications (MACs). The process is used to assess material quality and uniformity of a full 100 mm (4‐inch) wafer against the stringent target specifications. Yield and uniformity of devices are assessed in terms of optical power, differential efficiencies, and emission wavelength at 894.6 nm.